Putrajaya green cities : constraints and mitigation strategies towards low carbon cities - Abd. Razak, Mohd. Razif (2014)
The thesis presents the constraints and mitigation strategies that will be facing in making Putrajaya as Green Cities. As the Malaysian Government aspiration to reduce 40% of CO2 emission intensity by the year 2020 as compared to the 2005 as benchmark, a few actions have been taken to fulfill the aspiration. Two main contribution of Green House Gas (GHG) have been identified which are come from buildings and transportation. Effect of the action taken to reduce the GHG emission from this two sector will be discuss with the feedback from residents of Putrajaya will be taken in justification the result. As a result, it can be summarized that the action taken have to be review back in a few part to encourage the resident of Putrajaya to play the main role to make the Putrajaya as Green Cities success.